Human α-Defensins Inhibit BK Virus Infection by Aggregating Virions and Blocking Binding to Host Cells - Dugan, Aisling S. (American Society for Biochemistry and Molecular Biology, 2008)
BK virus (BKV) is a polyomavirus that establishes a lifelong persistence in most humans and is a major impediment to success of kidney grafts. The function of the innate immune system in BKV infection and pathology has not been investigated. Here we examine the role of antimicrobial defensins in BKV infection of Vero cells. Our data show that α-defensin human neutrophil protein 1 (HNP1) and human α-defensin 5 (HD5) inhibit BKV infection by targeting an early event in the viral lifecycle. HD5 treatment of BKV reduced viral attachment to cells, whereas cellular treatment with HD5 did not. Colocalization studies indicated that HD5 interacts directly with BKV. Ultrastructural analysis revealed HD5-induced aggregation of virions. HD5 also inhibited infection of cells by other related polyomaviruses. This is the first study to demonstrate polyomavirus sensitivity to defensins. We also show a novel mechanism whereby HD5 binds to BKV leading to aggregation of virion particles preventing normal virus binding to the cell surface and uptake into cells.